Anaphylactic reactions of ionic and nonionic contrasts during coronary angiogram - Saad, A; Zaffar, M; Bhutta, M; Ahmed, N; Almani, T; Azhar, M (2011)
Objective: To compare the acute anaphylactic reactions of ionic and nonionic contrasts in patients undergoing coronary angiogram. Study Design: Experimental Study. Place and Duration of Study: This study was conducted in Catheterization Laboratory of Punjab Institute of Cardiology, Lahore from 28th September 2007 to 27th March 2008. Materials and methods: 200 patients undergoing coronary angiogram, admitted in Punjab Institute of Cardiology Lahore through outpatient department (OPD) and emergency ward were included. The socio demographic information like name, age sex and address were recorded. After taking informed consent, the patients were divided into two groups by using random numbers table before the procedure. First group received ionic and the second group received nonionic dye. All patients will undergo coronary angiogram and anaphylactic reactions were recorded. Results: Out of 200 patients 153(76.5%) were male and 47(23.5%) were female .Age range was 32-75 yrs with mean age of 53.94±10.07 of study population .The study population was divided into two equal groups. First group 100 patients received Ionic dye while second group100 patients received Non ionic dye .Anaphylactic complications during coronary angiogram were more common in patients who received ionic contrast as compared to non ionic contrast group. Conclusion: Anaphylactic complications during coronary angiogram were more common with ionic dye as compared to non ionic contrast.